2022
DOI: 10.1097/hp.0000000000001625
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Radiofrequency Electromagnetic Fields above 100 MHz on Fauna and Flora: Workshop Report

Abstract: This report summarizes the effects of anthropogenic radiofrequency electromagnetic fields with frequencies above 100 MHz on flora and fauna presented at an international workshop held on 5-7 November 2019 in Munich, Germany. Anthropogenic radiofrequency electromagnetic fields at these frequencies are commonplace; e.g., originating from transmitters used for terrestrial radio and TV broadcasting, mobile communication, wireless internet networks, and radar technologies. The effects of these radiofrequency fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Numerous studies have shown that non-uniform magnetic fields can introduce variations in the response of biological systems, affecting the results of controlled biotechnological experiments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. By addressing non-uniformity through polygonal coil designs and dimension adjustments, the understanding and applicability of electromagnetic technologies in various biotechnology studies can be advanced [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that non-uniform magnetic fields can introduce variations in the response of biological systems, affecting the results of controlled biotechnological experiments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. By addressing non-uniformity through polygonal coil designs and dimension adjustments, the understanding and applicability of electromagnetic technologies in various biotechnology studies can be advanced [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research indicates that electromagnetic fields can stimulate or inhibit different biological systems [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], such as the growth of plants [ 13 ], fruits [ 14 ], and microorganisms [ 15 ]. Similarly, they affect cells in the human [ 16 ] and animal [ 17 ] body by stimulating or inhibiting different cellular processes [ 18 ]. Several of these cellular properties have been used to improve health [ 4 ], obtain metabolites of industrial interest [ 5 ], and remove contaminants from soil [ 6 ], water [ 7 ], and air [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total E-field strength in all cases is no more than 91 dB mu V/m. Pophof et al [16] investigated the biological effects of RF-EMF on fauna and flora. This area is not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile communication networks have become increasingly pervasive in the environment, in both urban and remote natural areas, leading to unprecedented wildlife exposure to radiofrequency electromagnetic fields (RF-EMFs; 100 kHz to 300 GHz) . RF-EMFs have the potential to exert a wide range of biological effects on wildlife, ranging from reduction in bat feeding activity and the alteration of life-history characteristics in insects to morphological abnormalities in plants. Different mechanisms have been proposed that could underlie these effects, including tissue heating and microwave hearing in animals or an increase in the rate of reactive oxygen species metabolism and level of cytosolic calcium in plants.…”
mentioning
confidence: 99%